EVALUASI KURIKULUM DAN PEMBELAJARAN: TINJAUAN SISTEMAIK LITERATUR DALAM MENJAWAB TANTANGAN PENDIDIKAN ABAD 21 - Bayo Hadomuan Tanjung; Agus Pahrudin; Sri Rahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Evaluation is a process that is very important to carry out when you want to know the achievement of an activity towards the activity goals that have been set at the beginning, including in the curriculum and learning process. Based on this, this article aims to determine the importance of evaluation and learning in the educational process. To fulfill this objective, researchers conducted research in several journals that discuss curriculum and learning evaluation.  This article uses a qualitative descriptive method, namely a research method that uses qualitative data which will then be presented descriptively. Research findings show that curriculum and learning evaluation is very important for educational units to determine the achievement of educational goals by educational units, including the teaching staff within them. This will then provide important information that can be used for further policy making to achieve educational goals.